Pemasangan Delineator Reflektif Mandiri sebagai Solusi Penerangan Pasif bagi Pengendara di RT 21 Kelurahan Penajam Kabupaten Penajam Paser Utara - Lina Yuliana; Mario Kristiandi; Rifqi Gandhie Pratama Husni Putra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Traffic safety in residential areas is often neglected due to the lack of street lighting infrastructure, as is the case in RT 21, Penajam Village, Penajam Paser Utara Regency. The lack of visibility at night in critical locations has increased the risk of accidents and reduced the sense of security for local residents. This community service activity aims to provide a passive lighting solution through the manufacture and installation of self-contained reflective delineators made from PVC pipes combined with reflector stickers. The delineators are designed with cement and sand mixture reinforcement on the inside, and casting on the base to ensure the durability of the structure. The method used in the implementation of this service is a mixed method. The mixed method is an approach that combines or associates qualitative and quantitative forms. The results of the service show that the community response is very positive, where 70% of residents stated that the reflection of light from the reflector is very helpful in anticipating bends or road edges from a distance. The synergy between civil engineering and Occupational Safety and Health (K3) ensures that the resulting product is not only structurally sound, but also effective in ensuring the safety of road users.